Wendy Michallat. French Cartoon Art in the 1960s and 1970s: Pilote hebdomadaire and the Teenager Bande Dessinée. Leuven UP, 2018. - Stephanie Schechner (Studies in 20th & 21st Century Literature, 2019)
Review of Wendy Michallat. French Cartoon Art in the 1960s and 1970s: Pilote hebdomadaire and the Teenager Bande Dessinée. Leuven UP, 2018. 268 pp.
Keywords: French cartoon art; comics; Bande Dessinée